Pengaruh Kualitas Pelayanan Dan Harga Tambahan Layanan Terhadap Kepuasan konsumen Pengguna Jasa Kapal Penyebrangan Di PT Trisakti Lautan Mas Cabang Bakauheni, Lampung - Gugup Tugi Prihatma (Universitas Serang Raya, 2020)
Customer satisfaction will be formed if it can meet the expectations of the consumer base. Many factors that affect customer satisfaction including the quality of service and price. The problem in this research is (1) How does the quality of service to customer satisfaction, (2) How does the price of the additional services to customer satisfaction, (3) How does the quality of service and price of the additional services simultaneously on customer satisfaction. The results obtained by multiple linear regression equation Y = 13,122 + 0.159 X1 + 0.145 X2. Quality of service is not positive and not significant to customer satisfaction with the grades were t = 1.459, the price of the additional services are not there is positive and no significant effect on customer satisfaction with the value t = 1.441, quality of service and price of the additional services together no significant effect on consumer satisfaction with the value of F = 3.012. Overall quality of service and price of the additional services affect customer satisfaction by 0.048 or 4.8%, while the remaining 95.2% is influenced by other factors not examined by the author. Based on this research can be concluded that: 1) there are significant positive and significant correlation between quality of service to customer satisfaction 2) There is no influence of positive and significant correlation between the price of the additional services to customer satisfaction 3) there is positive and significant correlation between quality of service price additional services simultaneously on customer satisfaction.